Celexocib (200 MG/D) or diclofenac (100 MG/D) in osteoarthritis: A multicentre, double blind trial - Yazici, H; Ozdemir, O; Kirazli, Y; Ozbek, S; Ozerbil, O; Gur, A; Aral, O (B M J Publishing Group, 2003)
[Abstract Not Available]
Annual European Congress of Rheumatology -- JUN 18, 2003 -- LISBON, PORTUGAL